Representation of disability in visual media : a "tragedy" rocks Shortland Street : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Media Studies at Massey University - Moulton, Rebecca Elwyn (Massey University, 1998)
The focus of this research is to explore the portrayal of the disability image in visual media. Many disabled activists object to the stereotypical format that the media utilises to represent them and their disabilities, arguing that the images are offensive. Previous studies of cultural images of disability have focused on the inaccuracies of the stereotypes. However, the use of stereotypes leads to misconceptions about the experience of disability. The analysis in this thesis is exploratory, moving away from traditional analyses. A semiotic approach is applied to demonstrate how representation operates as a signifying practice that produces and reproduces the meanings of disability prevalent in media images. Findings suggest that the concept of 'disability' has a variety of constructed meanings that exist within the technical and compositional elements of the Shortland Street Multiple Sclerosis narrative. This is a pivotal point as it exposes the origins of the constructed meaning of disability and serves as a foundation for the reconceptualisation of an authentic image of disability. It is acknowledged by the broadcasting industry that there is a need to achieve authenticity of the representation of disability images in the media. One of the ways they believe this can be achieved is through increasing the opportunity for disabled actors to be cast in disability roles. Another possibility is incorporating disability into the media, not as an element of difference in a negative sense, but by authenticating the difference of disability. These possibilities have profound implications for the future of the disability image. But these implications raise further questions as to whether directors and producers of media will accept the challenge and portray disability as an authentic experience. More importantly, would such a development alter the meaning and perception of disability in Western society?
Keywords: Shortland Street (Television programme); People with disabilities on television; Portrayal of disabled; Stereotypes